PERBAIKAN SIFAT LIST PROFILE LIMBAH SERAT KELAPA DENGAN PERLAKUAN JENIS DAN JUMLAH PEREKAT - Sushardi; Siman Suwadji, Hastanto BW dan Didik Surya Hadi (PROSIDING, 2022)
. List profile is a mineral board product that is increasingly in demand by the wider community. One of the advantages is that the list profile is cheap, quick to get it, resistant to attacks by wood-destroying organisms and can be obtained in the form of attractive ornaments. In terms of economy, the list profile with cast adhesives is more expensive, so other types of adhesives that have the same strength as low prices are needed. This study aims to determine the type and adhesive content of casts, white cement and their mixture against the properties of the list profile. The study used a complete randomized design with a further tukey trial. The factors used are the type of adhesive (cast, white cement and a mixture of the cast with white cement) and the amount of adhesive (600 g, 690 g and 780 g). The observed parameters are moisture content, density, fractured modulus and internal adhesiontre. The results showed that the type and amount of adhesive had no real effect on the parameters of the fracture modulus and the firmness of the internal adhesive list profile, while the type of adhesive had a real effect on the moisture content and the amount of adhesive had a noticeable effect on the density. Moisture content value 14.86 - 20.57 %, density 0.61- 0.94 g/cm3, fractured modulus 18.06 - 37.39 kg/cm2 and internal adhesion constancy 6.07- 12.51 kg/cm2. Coconut fiber waste can be used as a filler for list profiles, the results of the list profile research all meet the Indonesian National Standards and Japanese Standar except water content. Keywords: List profile, cast, white cement, adhesive content